Manajemen Pengembangan Barang Milik Negara Sebagai Upaya Dalam Meningkatkan Layanan Pendidikan Pada Satuan Kerja Madrasah Tsanawiyah Negeri 7 Tulungagung - Setyandari, Yuliana Ika; Askafi, Eka (Otonomi, 2025)
In the current digitalization era, advances in information technology are developing very rapidly. In order to create optimal, efficient and effective control and supervision of state property management, this study aims to: (1) To determine and analyze the management development of state property as an effort to improve educational services at Madrasah Tsanawiyah Negeri 7 Tulungagung. (2) To find out and analyze the supporting factors and inhibiting factors of the management development of state property as an effort to improve educational services at the Madrasah Tsanawiyah Negeri 7 Tulungagung. This study uses a qualitative analysis method, namely research that seeks to find and obtain in-depth information from the amount of information. While the quality test uses (1) Data collection, (2) Data reduction, (3) Data display, and (4) Conclusion (verification). The results of the study indicate that: (1) Management Development of State Property as an Effort to Improve Education Services at Madrasah Tsanawiyah Negeri 7 Tulungagung , includes: (a) Planning, (b) Procurement, (c) Maintenance, and (d) Deletion. (2) Supporting factors, include: (a) SOP and policies, (b) Optimizing the Utilization of BMN, (c) Adding HR for Appraisers, (d) Regulation Evaluation. While inhibiting factors, include: (a) Not all assets that can be utilized have been inventoried, (b) HR that is not yet reliable and professional including the lack of HR for appraisers, (c) BMN management is not optimal (administration, security, maintenance, security and utilization), (d) Not all utilization cooperation has been made SOP and regulations that are not in accordance with existing conditions.